Beethoven in his study - Schlösser, Carl Bernhard, 1832-after 1914 (artist):::Creator:::::::::::: (The Fine Art Society; England; London)
Reproduction of lithograph by Schlösser depicting Beethoven in his study at the Schwarzspanierhaus in Vienna; his Broadwood piano is cluttered with musical scores. See similar item at g2b014 and color version at g2b121.